Work Burnout and Engagement Profiles Among Teachers - Salmela-Aro, Katariina; Hietajärvi, Lauri; Lonka, Kirsti (Frontiers in Psychology, 2019)
The focus of the current study was to examine teachers’ well-being in terms of work engagement and burnout by using a person-oriented approach. The participants (n = 149, 70.5 % female) were subject-matter teachers from 22 schools from metropolitan Helsinki area in Finland. The first aim was to examine the kinds of profiles we can identify based on work burnout and engagement among teachers. The second aim was to study how the identified profiles differed in job-related demands and resources and personal resources in terms of resilience. Based on the demands-resources model, we expected to find profiles that differ in terms of key resources and demands. The sample was acquired as a convenience sample and the data was collected using online self-report questionnaires. The measures were work engagement, work burnout, work demands/resources (workload and control) and resilience as the personal resource. In addition, changes and effects of the economic circumstances were accounted for with two binary variables assessing the effect on class sizes and material resources. We identified two profiles among teachers: engaged (30 %) and engaged-burnout (70 %) profiles. We found that those in the engaged profile group had more job and personal resources, such as control and resilience, whereas those in the engaged-burnout profile group experienced more work demands, such as workload.